2014
DOI: 10.1038/nn.3669
|View full text |Cite
|
Sign up to set email alerts
|

Broadly tuned and respiration-independent inhibition in the olfactory bulb of awake mice

Abstract: Olfactory representations are shaped by brain state and respiration. The interaction and circuit substrates of these influences are unclear. Granule cells (GCs) in the main olfactory bulb (MOB) are presumed to sculpt activity reaching the cortex via inhibition of mitral/tufted cells (MTs). GCs potentially make ensemble activity more sparse by facilitating lateral inhibition among MTs and/or enforce temporally precise activity locked to breathing. Yet the selectivity and temporal structure of wakeful GC activit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 57 publications
(49 reference statements)
5
64
0
Order By: Relevance
“…We found that, consistent with previous reports of the effects of anesthesia on GC somata (Cazakoff et al, 2014; Kato et al, 2012), abGC dendrites are more responsive and broadly tuned in the awake state. Interestingly, this effect was more pronounced in young abGC dendrites, resulting in a more dramatic difference between young and mature cells in awake mice compared to mice anesthetized with ketamine/xylazine.…”
Section: Discussionsupporting
confidence: 92%
“…We found that, consistent with previous reports of the effects of anesthesia on GC somata (Cazakoff et al, 2014; Kato et al, 2012), abGC dendrites are more responsive and broadly tuned in the awake state. Interestingly, this effect was more pronounced in young abGC dendrites, resulting in a more dramatic difference between young and mature cells in awake mice compared to mice anesthetized with ketamine/xylazine.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the transition from the awake to anesthetized condition strongly reduces bulbar interneuron activity and enhances odor-evoked mitral cell output (Cazakoff et al, 2014; Kato et al, 2012; Wachowiak et al, 2013). How does cortical feedback input respond to this change in brain state?…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, wakefulness strongly increases the activity of olfactory bulb interneurons (Cazakoff et al, 2014; Kato et al, 2012; Wachowiak et al, 2013). For example, granule cells are predominantly inactive in the anesthetized state, but have high amounts of spontaneous activity and more broadly-tuned odor responses during wakefulness (Cazakoff et al, 2014; Kato et al, 2012). One explanation for the opposite changes in PCx and mitral cell activity is that brain state-dependent changes in interneuron activity are directly inherited from their PCx feedback input.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory processing in the main olfactory system is clearly altered by anesthesia level and behavioral state (Rinberg et al, 2006; Cazakoff et al, 2014), and relating the findings from the current study to data from behaving animals will be an important step for future studies.…”
Section: Discussionmentioning
confidence: 96%